2001
DOI: 10.1034/j.1600-0773.2001.d01-162.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of the Alkaloids Harman and Harmine Assessed by Comet Assay and Chromosome Aberration Test in Mammalian Cells in vitro

Abstract: Harman and harmine are b-carboline alkaloids which are present in plants widely used in medical practice, in beverages used for religious purposes in Brazil, as well as in tobacco smoke and over cooked food. In view of the controversial results observed in the literature about the mutagenic effects of these alkaloids, we studied their cytotoxic and genotoxic effects in V79 Chinese hamster lung fibroblasts in vitro using single-cell gel assay, Comet assay, either in the presence or in absence of an exogenous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 40 publications
0
37
0
2
Order By: Relevance
“…The Tukey test was applied for post-hoc comparison. A cytotoxic response was considered when the viability values observed were below 70%, when compared to the control (Boeira et al, 2001;Cardozo et al, 2006;Žegura et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The Tukey test was applied for post-hoc comparison. A cytotoxic response was considered when the viability values observed were below 70%, when compared to the control (Boeira et al, 2001;Cardozo et al, 2006;Žegura et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic and genotoxic effects of harmine were investigated in V79 Chinese hamster lung fibroblasts in vitro using singlecell gel assay, also known as Comet assay, and the results showed that harmine increased aberrant cell frequency and induced DNA damage as evidenced by the Comet assay [35] . Effects of harmine on yeast Saccharomyces cerevisiae were investigated to verify putative genotoxicity, mutagenicity and recombinogenicity.…”
Section: Effect Of Harmine Against Cancermentioning
confidence: 99%
“…The colonies were fixed with methanol-acetic acid (3:1) and stained with 0.1% violet crystal. Any sample that presented a number of colonies equal to or less than 70% of the number of colonies in the negative control was considered cytotoxic (Speit et al 1998;Boeira 2001).…”
Section: Methodsmentioning
confidence: 99%